Effects of Rhizobacteria Inoculation on Germination and Physiology Status of Tomato under Salt Stress - Khaled, Boufares; Mostefa, Kouadria; Naima, Merdjet Yahia; Abdelwahab, Benali (Annals of Arid Zone, 2022)
The aim of this work is to explore the effect of inoculation with native rhizobacteria strains isolated from steppe ecosystems on enhancing salt tolerance of tomato (Solanum lycopersicum L.). For this purpose, various rhizobacteria strains have been purified, identified, and then applied on tomato seeds, in vitro then in pots to study their effects on the germination parameters and growth under salt stress. Eight genera of rhizobacteria strains were identified; they displayed pertinent plant growth promotion features such as phytohormones biosynthesis, fixation of atmospheric nitrogen, and phosphate solubilization. The obtained results demonstrated that salinity negatively affected seed germination and impaired plant growth. In response to salt stress, uninoculated plants accumulated a significant amount of osmoregulators (proline and glycine betaine), and recorded a decrease in their chlorophyll content, compared to inoculated plants, where the salinity tolerance has been much better with a high seedling growth as well as high chlorophyll and low osmolyte contents. Among the eight strains used in this study, three (Agrobacterium, Citrobacter and Enterobacter) demonstrated their effectiveness in enhancing salt tolerance of tomato plants. The use of native rhizobacteria strains as biofertilizer could be a sustainable approach to improve plant growth in salinity-impacted regions.